Discontinuation of non-Vitamin K antagonist oral anticoagulants in patients with non-valvular atrial fibrillation: a population-based cohort study using primary care data from The Health Improvement Network in the UK. Issue 10 (18th October 2019) - Ruigómez, Ana; Vora, Pareen; Balabanova, Yanina; Brobert, Gunnar; Roberts, Luke; Fatoba, Samuel; Fernandez, Oscar; García Rodríguez, Luis Alberto
Abstract : Objective: To determine discontinuation rates, patterns of use and predictors of discontinuation of non-vitamin K antagonist oral anticoagulants (NOACs) among patients with non-valvular atrial fibrillation (NVAF) in the first year of therapy. Design: Population-based cohort study. Setting: UK primary care. Population: 11 481 patients with NVAF and a first prescription (index date) for apixaban, dabigatran or rivaroxaban (January 2012 to December 2016) with at least 1 year of follow-up and at least one further NOAC prescription in the year following the index date were identified. 1 year rates and patterns of discontinuation were described. Primary and secondary outcome measures: Outcome measures were the percentage of patients who, in the first year from starting NOAC therapy, discontinued with their oral anticoagulant (OAC) therapy (discontinuation was defined as a gap in OAC therapy of >30 days); switched OAC within 30 days; discontinued and reinitiated OAC therapy. Predictors of discontinuation were also evaluated. Results: 1 year discontinuation rates according to the index NOAC were 26.1% for apixaban, 40.0% for dabigatran and 29.6% for rivaroxaban. Reinitiation rates were 18.1% for apixaban, 21.7% for dabigatran and 17.3% for rivaroxaban, and switching rates were 2.8% for apixaban, 8.8% for dabigatran and 4.9% for rivaroxaban. More than 93% of reinitiations were with the index NOAC. Patients starting on dabigatran were more likely to switch OAC therapy than those starting on apixaban; ORs 4.28 (95% CI 3.24 to 5.65) for dabigatran and 1.89 (95% CI 1.49 to 2.39) for rivaroxaban. Severely reduced renal function was a predictor of any discontinuation, OR 1.77 (95% CI 1.28 to 2.44). Conclusion: While the majority of patients with NVAF in the UK initiating NOAC treatment received continuous therapy in the first year of treatment, a substantial proportion of patients experienced gaps in treatment leaving them less protected against thromboembolism during these periods.